PENANGGULANGAN ANAK JALANAN BERBASIS COMMUNITY DEVELOPMENT DI KOTA SERANG - Budi Hasanah; Liza Diniarizky Putri (NATAPRAJA, 2019)
Children must receive good education, positive parenting, protection and other rights so that they can growth properly. But actually, it did not happen in Kota Serang. It was caused by the increasing number of street children. There were increasing number of street children in 2016, 31 children so until now the total was 181 children. This research was about the prevention of street children based on community development with conflict theme and intervention model. This research used biddle theory with three indicators: explanatory, organizational and discussional.  This research used qualitative with descriptive method. The data from interview and deep discussion as well as observation used interactive model analysis. The results showed that there were some factors behind the number of street children in Kota Serang. Based on the FGD results, an alternative solution was need to reactivation the existing halfway house and form special team to take care the childreen who live there. Thus, the prevention of street childreen based on community development program could be run effectively.